The Financial Systems of Financially Less Developed Asian Economies: Key Features and Reform Priorities - Aaron Batten; Poullang Doung; Enerelt Enkhbold; Gemma Estrada; Jan Hansen; George Luarsabishvili; Md. Golam Mortaza; Donghyun Park (Asian Development Bank (ADB), 2015)
Developing Asia's financial depth as a whole compares favorably with other parts of the developing world, but there are wide variations across subregions and economies. This paper examines the key features and reform priorities of the financial systems in Bangladesh, Cambodia, Georgia, Mongolia, and Papua New Guinea. All are low-income and lower-middle-income economies that have relatively underdeveloped systems heavily dominated by banks and with low levels of access, especially for the poor. The urgent priority for bank-dominated economies is creating a more competitive environment that mobilizes domestic savings, lowers the cost of capital, improves access, and channels credit to the most productive sectors. Reforming state-owned or state-linked banks can also yield sizable efficiency gains. A common need in all five is good governance in financial institutions and markets. Financial regulators in these countries face a difficult trade-off between promoting economic growth and safeguarding financial stability.
hdl:11540/5145
Keywords: G20; G28; 330; financial development; financial system; low-income economies; lower-middle-incomeeconomies